Development of MIMO antenna with decoupling structure for ultra-wideband application - Muhammad Aslam Hasin; M. T. Ali; Hamizan Yong; Bazilah Baharom; Hadi Jumaat (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the design of adouble-sided Multiple-Input Multiple-Output (MIMO) antenna with a decoupling structure for Ultra-WideBand (UWB) applications. The proposed antenna consists of four square radiating elements printed on FR-4 substrate with partial slotted ground. The substrate consists of two sides and each side are consisting of two slotted partial ground and two square radiator antennas. The elements of the front side are orthogonal to the elements of the back side because it was to increase the isolation of the antenna. The front and back sides of the substrate were also presented with the decoupling structure to avoid the mutual coupling of each antenna. The results of simulated and measured of the proposed UWB MIMO antenna are observed and analyzed. The objective of the UWB MIMO antenna was achieved that large bandwidth of return loss below than -10 dB from 3.3 GHz to 11GHz with an insertion loss lower than -20 dB within the required frequency band. The proposed MIMO antennas exhibits a nearly Omni-directional radiation pattern with average gain value 4.36 dBi.